Biochemistry of connective tissue. Biochemistry of mixed saliva: учебное пособие для использования в образовательных учреждениях, реализующих основные профессиональные образовательные программы высшего образования по направлению подготовки специалитета по специальности 31.05.03 "Стоматология" - Глухов, А. И. Александр Иванович (Tutorial, 2019)
This tutorial contains information about the connective tissue chemical structure and metabolism, as well as the oral fl uid chemical composition and functions. The book reviews the issues of dental caries and periodontal diseases pathogenesis. The manual consists of two parts and includes clinical cases. The tutorial is designed for students of specialty "Dentistry" studying biochemistry in English. The book was prepared in accordance with the curriculum approved by the Educational Board of the Faculty of Dentistry, I.M. Sechenov First Moscow State Medical University.